Best Answer

3+10-r+6r = -3+9r+0 13+5r = -3+9r 16 = 4r r = 4

Q: What is 3 plus 10-r plus 6r equals -3 plus 9r plus 5-5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

What is ; -r-8+6r=-13.=]

r=8

5s-r

The 'solution' is the number that 'r' must be in order to make the statement true.Here's how to find it:6r - 1 + 6r = 11Add 1 to each side:6r + 6r = 12Clean up the left side:12r = 12Divide each side by 12:r = 1

3.333

Related questions

the answer is -10r

What is ; -r-8+6r=-13.=]

r=8

5s-r

The 'solution' is the number that 'r' must be in order to make the statement true.Here's how to find it:6r - 1 + 6r = 11Add 1 to each side:6r + 6r = 12Clean up the left side:12r = 12Divide each side by 12:r = 1

-6r-5 = 7-12r 12r-6r = 7+5 6r = 12 r = 2

3.333

12 - 6r = 2r + 36Add 6r to each side:12 = 8r + 36Subtract 36 from each side:-24 = 8rDivide each side by 8:r = -3

5 - 710 - 6r = -93-705 - 6r = -93 705 + 6r = 93 6r = 93 - 705 = -612 r = -612/6 = -102

Commutatitivity of addition in the fact that you can change the order of 11s and 3t. But also associativity of addition in that you can write the sum of three terms without the need for brackets to show which addition needs to be performed first.

21 4t2+6r-tr 4[-3]2+6[5]-[-3][5] 8[-3]+30-[-15] -24+30+15=21

-2r